A THEMATIC REVIEW ON FACTORS INFLUENCING TOPONYM TRANSLATION - Zhou , Yin; Abdul Halim, Hazlina; Nasir, Nur Yuhanis Mohd (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
Toponym translation is an interdisciplinary research field that integrates toponymy, linguistics, translation studies, literature, and sociology. While research on translation methods, strategies, and influencing factors has grown, there remains a lack of systematic reviews examining the key factors shaping toponym translation and the ways in which these factors influence translation practices. This study analyzes the research trends and mechanisms of influential factors in toponym translation as reflected in current literature. A thematic literature review method was employed in this study. Employing the keywords "toponyms" and "translation," 21 studies were selected from Scopus and Web of Science. Thematic analysis identified six primary factors: (1) cultural, historical, and geographical context; (2) political and ideological influences; (3) linguistic challenges; (4) norms and standards; (5) contextual and communicative factors; and (6) translation process and practice. Findings reveal that toponym translation is not merely a linguistic process but a complex interplay of social, political, and communicative forces. This review provides a structured framework for understanding these dynamics and highlights the need for further interdisciplinary research on the standardization and contextualization of toponym translation in global discourse.